IMPROVED PROBLEM SOLVING SKILLS SLOW LEARNER STUDENTS IN ELEMENTARY SCHOOL THROUGH THE USE OF CONSTRUCTIVISM LEARNING MODEL - Ali Asmar; Hafizah Delyana (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Tujuan penelitian ini adalah untuk mempelajari peningkatan kemampuan pemecahan masalah siswa SD yang termasuk dalam kategori lambat belajar yang menerapkan pembelajaran dengan menggunakan model pembelajaran konstruktivisme dan konvensional. Peneliti mengolah data menggunakan program SPSS 16 for Windows dan Microsoft Office Excel 2007 untuk mencapai tujuan tersebut. Subjek dalam penelitian ini adalah siswa slow learner kelas V SDN Adabiah Padang. Teknik pengumpulan data dengan observasi dan wawancara dengan pedoman observasi dan wawancara. Hasil penelitian menunjukkan bahwa melalui pre-test dan post-test keterampilan pemecahan masalah pada akhir pembelajaran menggunakan Model Pembelajaran Konstruktivisme dan pembelajaran konvensional. Data tes keterampilan pemecahan masalah diperoleh dari 16 siswa, 8 siswa kelas eksperimen yang menerapkan Model Pembelajaran Konstruktivisme, dan 8 siswa kelas kontrol yang menerapkan pembelajaran konvensional. Data tes keterampilan pemecahan masalah diperoleh dari 16 siswa, 8 siswa kelas eksperimen yang menerapkan Model Pembelajaran Konstruktivisme, dan 8 siswa kelas kontrol yang menerapkan pembelajaran konvensional. Penerapan model pembelajaran ini terjadi peningkatan keterampilan pemecahan masalah, termasuk pemahaman perencanaan masalah untuk pemecahan masalah berupa pemecahan masalah dari penerapan beberapa konsep pembelajaran matematika. Bukti dari data skor gain yang dinormalisasi (N-gain) antara kedua kelas dapat dilihat.The purpose of this study is to study the improvement of problem-solving skills of elementary students who fall into the category of slow learners who apply to learn using constructivism and conventional learning models. Researchers processed data using the SPSS 16 for Windows and Microsoft Office Excel 2007 programs to achieve these goals. The subjects in this study were students of slow learner class V Adabiah Padang Elementary School. Data collection techniques with observations and interviews with observation and interview guidelines. The results showed that through pre-test and post-test problem-solving skills at the end of learning using the Constructivism Learning Model and conventional learning. The problem-solving skills test data were obtained from 16 students, 8 experimental class students applying the Constructivism Learning Model, and 8 control class students who applied conventional learning. The problem-solving skills test data were obtained from 16 students, 8 experimental class students applying the Constructivism Learning Model, and 8 control class students who applied conventional learning. The application of this learning model occurs an increase in problem-solving skills, including understanding problem planning for problem-solving in the form of problem-solving from the application of several mathematical learning concepts. The evidence from data on normalized gain scores (N-gain) between the two classes may be seen.